Fibrinogen measurement in cardiac surgery with cardiopulmonary bypass: Analysis of repeatability and agreement of Clauss method within and between six different laboratories - Solomon, Cristina; Baryshnikova, Ekaterina; Tripodi, Armando; Schlimp, Christoph J.; Schöchl, Herbert; Cadamuro, Janne; Winstedt, Dag; Asmis, Lars; Ranucci, Marco (Thrombosis and Haemostasis, 2014)
Plasma fibrinogen concentration is important for coagulopathy assessment, and is most commonly measured using the Clauss method. Several factors, including device type and reagent, have been shown to affect results. The study objective was to evaluate performance and repeatability of the Clauss method and to assess differences between measurements performed during and after cardiopulmonary bypass (CPB), by testing plasma samples from patients undergoing cardiac surgery with CPB. Samples were collected from 30 patients before surgery, approximately 20 minutes before weaning from CPB, and 5 minutes after CPB and protamine. Fibrinogen concentration was determined using the Clauss method at six quality-controlled specialised laboratories, according to accredited standard operating procedures. Regarding within-centre agreement for Clauss measurement, mean differences between duplicate measurements were between 0.00 g/l and 0.15 g/l, with intervals for 95% limits of agreement for mean Bland-Altman differences up to 1.3 g/l. Regarding between-centre agreement, some mean differences between pairs of centres were above 0.5 g/l. Differences of up to ∼2 g/l were observed with individual samples. Increased variability was observed between centres, with inter-class correlation values below 0.5 suggesting only fair agreement. There were no significant differences in fibrinogen concentration before weaning from CPB and after CPB for most centres and methods. In conclusion, considerable differences exist between Clauss-based plasma fibrinogen measured using different detection methods. Nevertheless, the similarity between measurements shortly before weaning from CPB and after CPB within centres suggests that on-pump measurements could provide an early estimation of fibrinogen deficit after CPB and thus guidance for haemostatic therapy.
Keywords: Blood coagulation tests; clinical laboratory techniques; fibrinogen; nephelometry and turbidimetry; patient care management